Density Edelweis (Anaphalis javanica) In Mountain Burni Telong Bener Meriah - Milda - Gemasih; Djufri - Djufri (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Burni TelongMountain is among the mountains in Indonesia, which is the habitat of edelweiss (Anaphalis javanica). The existence of edelweiss in the Burni Telong mountains in recent years begun endangered because of encroachment by mountaineers. Based on this it is necessary to research on edelweis plant density in Burni Telong mountain. This study aims to determine the density of plants Anaphalis javanica in Burni Telong mountain highlands and to know abiotic factors affecting the edelweiss plant density. This research was conducted at Burni Telong Mountain in July 2016. The Advanced Research is descriptive quantitative. Sampling is done by dividing the three stations by different heights by making three sampling plots measuring 2m x 2m with three replications. Environmental factors observed include air temperature, light, humidity, and wind speed. The study found 1,435 edelweis/ha. All independent variables (temperature, light, humidity and wind speed) did not correlate closely to the independent variables (density edelweiss (Anaphalis javanica) in Burni Telong Mountain.